Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea. Issue 2 (17th February 2016) - Hong-Bo, Zheng; Pin, Yan; Wang, Yan-Lin; Xing, Yu-Qing
Abstract : Many researchers have focused on the characteristics of tectonic evolution in the Reed area of the southern South China Sea, but there has been little research focusing on deep-water sedimentary characteristics. Seismic data acquired in the Reed area have been processed and analyzed; representative deep-water sedimentary patterns, such as sediment waves, deep-water channels, slumping, and sliding mass, can be clearly distinguished from these seismic profiles. Combining this data with the geological setting and seafloor topography of the research area, it can be concluded that deep-water channels, slumping, and sliding depositions which have developed on the continental slope of the northeast Reed basin were formed by gravity flow, and the sediment waves which occur in the west and northwest Reed basin have been generated by deep-water bottom current.